Prediction of the distribution of segregation ice in the Mars regolith with Mg(ClO4)2 salts - Denis Lacelle; David Fisher; Wayne Pollard; Michael Daly; Isaac Smith; Hanna Sizemore (Icarus, 2026)

Does fishery management for groupers (Teleostei: Epinephelidae) protect them effectively? Context from the IUCN's Red list of threatened species - Sean T. Fennessy; Christi Linardich; Kevin Rhodes; Joao P. Barreiros; David Pollard; Eloy Sosa-Cordero; Felicia Coleman; Alfonso Aguilar-Perera; Christopher R. Malinowski; Thierry Brulé; Pedro Afonso; Kayan Ma; et al. (Ocean & Coastal Management, 2026)

A modern scientific methodology for structural geology - David D. Pollard; Stephen R. Pollard (Journal of Structural Geology, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Influences of aerosols and thin cirrus clouds on GOSAT XCO 2 and XCH 4 using Total Carbon Column Observing Network, sky radiometer, and lidar data - Tran Thi Ngoc Trieu; Isamu Morino; Osamu Uchino; Yukitomo Tsutsumi; Tetsu Sakai; Tomohiro Nagai; Akihiro Yamazaki; Hiroshi Okumura; Kohei Arai; Kei Shiomi; David F. Pollard; Ben Liley (International Journal of Remote Sensing, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The role of internal climate variability in projecting Antarctica’s contribution to future sea-level rise - Chii-Yun Tsai; Chris E. Forest; David Pollard (Climate Dynamics, 2020)
Retreat of the Antarctic ice sheet (AIS) is likely to be a major contributor to future sea-level rise (SLR). Current projections of SLR due to ice-sheet mass loss remain highly uncertain. Better understanding of how ice sheets respond to future climate forcing and variability is essential for assessing long-term risk of SLR. However, predictability of future climate is limited by uncertainties from emission scenarios, model structural differences, and internal climate variability (ICV) that is inherently generated within the fully coupled climate system. Among those uncertainties, the impact of ICV on the AIS changes has not been explicitly assessed. Here we quantify the effects of ICV on the AIS evolutions by employing climate fields from two large-ensemble experiments using the Community Earth System Model to force a three-dimensional ice-sheet model. We find that ICV of climate fields among ensemble members leads to significantly different AIS responses, and that most of the effect is due to atmospheric variability compared to oceanic. Our results show that ICV can cause about 0.08 m differences of AIS contribution to SLR by 2100 compared to the ensemble-mean AIS contribution of 0.38–0.45 m. Moreover, using ensemble-mean climate forcing fields as the forcing in an ice-sheet model significantly delays retreat of the West AIS for up to 20 years and significantly underestimates the AIS contribution to SLR by 0.07–0.11 m in 2100 and up to 0.34 m in the 2250’s. This study highlights the need to take internal climate variability into account in assessing uncertainty associated with the AIS contribution in sea-level rise projections.

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

South Polar Skua breeding populations in the Ross Sea assessed from demonstrated relationship with Adélie Penguin numbers - Deborah J. Wilson; Philip O’B. Lyver; Terry C. Greene; Amy L. Whitehead; Katie M. Dugger; Brian J. Karl; James R. F. Barringer; Roger McGarry; Annie M. Pollard; David G. Ainley (Polar Biology, 2017)

Jointing around magmatic dikes as a precursor to the development of volcanic plugs - Meredith Townsend; David D. Pollard; Kendra Johnson; Cansu Culha (Bulletin of Volcanology, 2015)

Comment on Bachmann et al. (2013): A nonrepresentative sample cannot describe the extent of cultural eutrophication of natural lakes in the United States - Cory P. McDonald; Noah R. Lottig; John L. Stoddard; Alan T. Herlihy; Sarah Lehmann; Steven G. Paulsen; David V. Peck; Amina I. Pollard; R. Jan Stevenson (Limnology and Oceanography, 2014)

Fishing groupers towards extinction: a global assessment of threats and extinction risks in a billion dollar fishery - Yvonne Sadovy de Mitcheson; Matthew T Craig; Athila A Bertoncini; Kent E Carpenter; William W L Cheung; John H Choat; Andrew S Cornish; Sean T Fennessy; Beatrice P Ferreira; Philip C Heemstra; Min Liu; Robert F Myers; et al. (Fish and Fisheries, 2013)
Groupers are a valuable fishery resource of reef ecosystems and are among those species most vulnerable to fishing pressure because of life history characteristics including longevity, late sexual maturation and aggregation spawning. Despite their economic importance, few grouper fisheries are regularly monitored or managed at the species level, and many are reported to be undergoing declines. To identify major threats to groupers, the International Union for Conservation of Nature (IUCN) Red List criteria were applied to all 163 species. Red List assessments show that 20 species (12%) risk extinction if current trends continue, and an additional 22 species (13%) are considered to be Near Threatened. The Caribbean Sea, coastal Brazil and Southeast Asia contain a disproportionate number of Threatened species, while numerous poorly documented and Near Threatened species occur in many regions. In all, 30% of all species are considered to be Data Deficient. Given that the major threat is overfishing, accompanied by a general absence and/or poor application of fishery management, the prognosis for restoration and successful conservation of Threatened species is poor. We believe that few refuges remain for recovery and that key biological processes (e.g. spawning aggregations) continue to be compromised by uncontrolled fishing. Mariculture, through hatchery‐rearing, increases production of a few species and contributes to satisfying high market demand, but many such operations depend heavily on wild‐caught juveniles with resultant growth and recruitment overfishing. Better management of fishing and other conservation efforts are urgently needed, and we provide examples of possible actions and constraints.

The Arctic Coastal Dynamics Database: A New Classification Scheme and Statistics on Arctic Permafrost Coastlines - Hugues Lantuit; Pier Paul Overduin; Nicole Couture; Sebastian Wetterich; Felix Aré; David Atkinson; Jerry Brown; Georgy Cherkashov; Dmitry Drozdov; Donald Lawrence Forbes; Allison Graves-Gaylord; Mikhail Grigoriev; et al. (Estuaries and Coasts, 2012)

Late Pliocene to Pleistocene sensitivity of the Greenland Ice Sheet in response to external forcing and internal feedbacks - Sebastian J. Koenig; Robert M. DeConto; David Pollard (Climate Dynamics, 2011)

A retrospective look at coupled ice sheet–climate modeling - David Pollard (Climatic Change, 2010)

Influence of Outcrop Scale Fractures on the Effective Stiffness of Fault Damage Zone Rocks - W. Ashley Griffith; Pablo F. Sanz; David D. Pollard (Pure and Applied Geophysics, 2009)

Constraining Surface Interpolations Using Elastic Plate Bending Solutions with Applications to Geologic Folding - J. Ole Kaven; Rafe Mazzeo; David D. Pollard (Mathematical Geosciences, 2009)

Eastern US Continental Shelf Carbon Budget: Integrating Models, Data Assimilation, and Analysis - Eileen Hofmann; Jean-Nöel Druon; Katja Fennel; Marjorie Friedrichs; Dale Haidvogel; Cindy Lee; Antonio Mannino; Charles McClain; Raymond Najjar; John O'Reilly; David Pollard; Michael Previdi; et al. (Oceanography, 2008)

A genome-wide approach to identifying novel-imprinted genes - Katherine S. Pollard; David Serre; Xu Wang; Heng Tao; Elin Grundberg; Thomas J. Hudson; Andrew G. Clark; Kelly Frazer (Human Genetics, 2008)

Optical mapping of V m and Cai 2+ in a model of arrhythmias induced by local catecholamine application in patterned cell cultures - David Z. Lan; Andrew E. Pollard; Stephen B. Knisley; Vladimir G. Fast (Pflügers Archiv - European Journal of Physiology, 2007)

Landscape-scale Variation in Taxonomic Diversity in Four Groups of Aquatic Organisms: The Influence of Physical, Chemical, and Biological Properties - Thomas R. Hrabik; Ben K. Greenfield; David B. Lewis; Amina I. Pollard; Karen A. Wilson; Timothy K. Kratz (Ecosystems, 2005)

Palaeotemperature reconstructions of the European permafrost zone during marine oxygen isotope Stage 3 compared with climate model results - Ko van Huissteden; Jef Vandenberghe; David Pollard (Journal of Quaternary Science, 2003)
A palaeotemperature reconstruction based on periglacial phenomena in Europe north of approximately 51 °N, is compared with high‐resolution regional climate model simulations of the marine oxygen isotope Stage 3 (Stage 3) palaeoclimate. The experiments represent Stage 3 warm (interstadial), Stage 3 cold (stadial) and Last Glacial Maximum climatic conditions. The palaeotemperature reconstruction deviates considerably for the Stage 3 cold climate experiments, with mismatches up to 11 °C for the mean annual air temperature and up to 15 °C for the winter temperature. However, in this reconstruction various factors linking climate and permafrost have not been taken into account. In particular a relatively thin snow cover and high climatic variability of the glacial climate could have influenced temperature limits for ice‐wedge growth. Based on modelling the 0 °C mean annual ground temperature proves to be an appropriate upper temperature limit. Using this limit, mismatches with the Stage 3 cold climate experiments have been reduced but still remain. We therefore assume that the Stage 3 ice wedges were generated during short (decadal time‐scale) intervals of extreme cold climate, below the mean temperatures indicated by the Stage 3 cold climate model simulations. Copyright © 2003 John Wiley & Sons, Ltd.

Two Reproductive Life History Types of Kokanee, Onchorynchus nerka, Exhibit Multivariate Morphometric and Protein Genetic Differentiation - Gary A. Winans; Susan Pollard; David R. Kuligowski (Environmental Biology of Fishes, 2003)

Modeling Global Climate–Vegetation Interactions in a Doubled CO2 World - Jon C. Bergengren; Starley L. Thompson; David Pollard; Robert M. DeConto (Climatic Change, 2001)

GCM-simulated hydrology in the Arctic duringn the past 21,000 years - Benjamin Felzer; Starley Thompson; David Pollard; Jon Bergengren (Journal of Paleolimnology, 2000)

Threatened Fishes of the World: Carcharias taurus (Rafinesque, 1810) (Odontaspididae) - Adam K. Smith; David A. Pollard (Environmental Biology of Fishes, 1999)

On the stability of the high‐latitude climate‐vegetation system in a coupled atmosphere‐biosphere model - Samuel Levis; Jonathan A. Foley; Victor Brovkin; David Pollard (Global Ecology and Biogeography, 1999)
Summary In order to investigate the hypothesis that the Earth's climate and vegetation patterns may have more than one basic state, we use the fully coupled GENESIS‐IBIS model. GENESIS is an atmospheric general circulation model. IBIS is a dynamic global vegetation model that integrates biophysical, physiological, and ecological processes. GENESIS and IBIS are coupled by way of a common land surface interface to allow for the full and transient interaction between changes in the vegetation structure and changes in the general circulation of the atmosphere. We examine two modern climate simulations of the coupled model initialized with two different initial conditions. In one case, we initialize the model vegetation cover with the modern observed distribution of vegetation. In the other case, we initialize the vegetation cover with evergreen boreal forests extending to the Arctic coast, replacing high‐latitude tundra. We interpret the coupled model's behaviour using a conceptual model for multistability and demonstrate that in both simulations the climate‐vegetation system converges to the same equilibrium state. In the present climate, feedbacks between land, ocean, sea ice, and the atmosphere do not result in the warming required to support an expanded boreal forest.

The effect of high altitude on platelet counts, thrombopoietin and erythropoietin levels in young Bolivian airmen visiting the Andes - J. G. Hudson; Angela L. Bowen; Pilar Navia; Jaime Rios-Dalenz; Andrew J. Pollard; David Williams; Donald Heath (International Journal of Biometeorology, 1999)

Coupling dynamic models of climate and vegetation - JONATHAN A. FOLEY; SAMUEL LEVIS; COLIN I. PRENTICE; DAVID POLLARD; STARLEY L. THOMPSON (Global Change Biology, 1998)

Coupling dynamic models of climate and vegetation - Jonathan A. Foley; Samuel Levis; I. Colin Prentice; David Pollard; Starley L. Thompson (Global Change Biology, 1998)
Numerous studies have underscored the importance of terrestrial ecosystems as an integral component of the Earth's climate system. This realization has already led to efforts to link simple equilibrium vegetation models with Atmospheric General Circulation Models through iterative coupling procedures. While these linked models have pointed to several possible climate–vegetation feedback mechanisms, they have been limited by two shortcomings: (i) they only consider the equilibrium response of vegetation to shifting climatic conditions and therefore cannot be used to explore transient interactions between climate and vegetation; and (ii) the representations of vegetation processes and land‐atmosphere exchange processes are still treated by two separate models and, as a result, may contain physical or ecological inconsistencies. Here we present, as a proof concept, a more tightly integrated framework for simulating global climate and vegetation interactions. The prototype coupled model consists of the GENESIS (version 2) Atmospheric General Circulation Model and the IBIS (version 1) Dynamic Global Vegetation Model. The two models are directly coupled through a common treatment of land surface and ecophysiological processes, which is used to calculate the energy, water, carbon, and momentum fluxes between vegetation, soils, and the atmosphere. On one side of the interface, GENESIS simulates the physics and general circulation of the atmosphere. On the other side, IBIS predicts transient changes in the vegetation structure through changes in the carbon balance and competition among plants within terrestrial ecosystems. As an initial test of this modelling framework, we perform a 30 year simulation in which the coupled model is supplied with modern CO 2 concentrations, observed ocean temperatures, and modern insolation. In this exploratory study, we run the GENESIS atmospheric model at relatively coarse horizontal resolution (4.5° latitude by 7.5° longitude) and IBIS at moderate resolution (2° latitude by 2° longitude). We initialize the models with globally uniform climatic conditions and the modern distribution of potential vegetation cover. While the simulation does not fully reach equilibrium by the end of the run, several general features of the coupled model behaviour emerge. We compare the results of the coupled model against the observed patterns of modern climate. The model correctly simulates the basic zonal distribution of temperature and precipitation, but several important regional biases remain. In particular, there is a significant warm bias in the high northern latitudes, and cooler than observed conditions over the Himalayas, central South America, and north‐central Africa. In terms of precipitation, the model simulates drier than observed conditions in much of South America, equatorial Africa and Indonesia, with wetter than observed conditions in northern Africa and China. Comparing the model results against observed patterns of vegetation cover shows that the general placement of forests and grasslands is roughly captured by the model. In addition, the model simulates a roughly correct separation of evergreen and deciduous forests in the tropical, temperate and boreal zones. However, the general patterns of global vegetation cover are only approximately correct: there are still significant regional biases in the simulation. In particular, forest cover is not simulated correctly in large portions of central Canada and southern South America, and grasslands extend too far into northern Africa. These preliminary results demonstrate the feasibility of coupling climate models with fully dynamic representations of the terrestrial biosphere. Continued development of fully coupled climate‐vegetation models will facilitate the exploration of a broad range of global change issues, including the potential role of vegetation feedbacks within the climate system, and the impact of climate variability and transient climate change on the terrestrial biosphere.

Boris A. Kagan, Ocean-Atmosphere Interaction and Climate Modelling - David Pollard (Climatic Change, 1998)